Rapid microbial production of long-lived dissolved organic carbon in the global ocean - Ruanhong Cai; Oliver J. Lechtenfeld; Andrew J. Tanentzap; Julian P. Sachs; Shuh‐Ji Kao; Helena Osterholz; Zhenwei Yan; Chen Zhao; Yuanbi Yi; Penghui Li; Chuanlun Zhang; Nianzhi Jiao; et al. (Proceedings of the National Academy of Sciences, 2026)
Marine microbes have long been regarded as central to replenishing the ocean’s reservoir of recalcitrant dissolved organic matter (RDOM). However, molecular-level evidence for their role remains inconclusive because RDOM persists for years to millennia, far exceeding timescales accessible to laboratory experiments, and because conventional analytical approaches lack the resolution to discern structural isomers of RDOM that confer functionally important differences in persistence. Using polarity-based liquid chromatography coupled to ultrahigh-resolution mass spectrometry capable of discriminating RDOM isomer clusters, we reveal that marine microbial consortia rapidly (≤ 90 d) convert diverse organic substrates into RDOM with extensive structural isomerism that closely mirrors natural seawater RDOM. A subset of these microbially derived RDOM compounds exhibits near-ubiquitous occurrence (> 99%) in a global dataset and accumulates progressively in the ocean’s interior. Together, our findings substantiate the direct microbial contribution to the long-lived oceanic carbon reservoir through the rapid diversification of RDOM isomers, a mechanism that contributes to sustaining the complexity and long-term persistence of the planetary-scale carbon reservoir.